The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-97332004000400039
|View full text |Cite
|
Sign up to set email alerts
|

MBE growth and characterization of Sn1-xEu xTe

Abstract: Epilayers of Sn1−xEuxTe (0 < x < 0.03) were grown by molecular beam epitaxy on freshly cleaved BaF 2 (111) substrates and their structural, electrical and optical properties were investigated. The thicknesses of epilayers were about 1.5 µm and deposition was carried out at growth temperatures of 300 o C. The structural properties were investigated by high resolution X-ray diffraction and a sharp film degradation could be observed with increasing europium content. Electrical measurements with temperature varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The patterns can be indexed in the cubic NaCl‐type structure, space group Fm‐3m , with no indication of the existence of a second phase. The calculated lattice parameter, a , of AgSn m SbTe m+2 increases with increasing m value consistent with the difference between the lattice parameter of SnTe (6.30 Å)15 and AgSbTe 2 (6.08 Å)16 (see Figure 1b). The melting points of the AgSn m SbTe m+2 samples determined by differential thermal analysis (DTA) are high, >1000 K (see Figure ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The patterns can be indexed in the cubic NaCl‐type structure, space group Fm‐3m , with no indication of the existence of a second phase. The calculated lattice parameter, a , of AgSn m SbTe m+2 increases with increasing m value consistent with the difference between the lattice parameter of SnTe (6.30 Å)15 and AgSbTe 2 (6.08 Å)16 (see Figure 1b). The melting points of the AgSn m SbTe m+2 samples determined by differential thermal analysis (DTA) are high, >1000 K (see Figure ).…”
Section: Resultssupporting
confidence: 77%
“…Given that, in the related material, TEM of Ag 0.85 SnSb 1. 15 Te 3 revealed extensive nanostructuring, [18] it is not unreasonable to anticipate similar behavior in AgSn m SbTe m+2 . Such an investigation goes beyond the scope of the present study and will be reported in the future.…”
Section: Resultsmentioning
confidence: 93%
“…8,9 There are some reports on the SnEuTe ternally alloy and EuTe/SnTe SL. [10][11][12] However, reduction in the carrier concentration has never been reported for this system. Thus, it is considered that the insertion of Eu strongly reduced the number of Sn vacancies in the SnTe layer, leading to the reduction in hole concentration and a drastic increase in hole mobility.…”
Section: Sntementioning
confidence: 80%
“…For the preparation of the EuTe films, two individual cells were used as Eu and Te 2 beam source and the growth rate was kept constant at ϳ1.3 Å / s. The EuTe͑111͒ epitaxial layers were grown at 175°C. The growth conditions have to be precisely controlled in order to obtain high quality and smooth EuTe epitaxial films grown in a two-dimensional layer-by-layer mode, 25 since the EuTe͑111͒ surface has a very strong tendency to a three-dimensional growth mode. 26 After the EuTe growth, the samples were transferred to a second MBE system and the Fe and the protective Cu layers were grown at room temperature.…”
Section: Methodsmentioning
confidence: 99%